Fragmentation of Care Among Black Women With Breast Cancer and Comorbidities: The Role of Health Systems. Issue 5 (May 2021) - Doose, Michelle; Sanchez, Janeth I.; Cantor, Joel C.; Plascak, Jesse J.; Steinberg, Michael B.; Hong, Chi-Chen; Demissie, Kitaw; Bandera, Elisa V.; Tsui, Jennifer
Abstract : PURPOSE: Black women are disproportionately burdened by comorbidities and breast cancer. The complexities of coordinating care for multiple health conditions can lead to adverse consequences. Care coordination may be exacerbated when care is received outside the same health system, defined as care fragmentation. We examine types of practice setting for primary and breast cancer care to assess care fragmentation. MATERIALS AND METHODS: We analyzed data from a prospective cohort of Black women diagnosed with breast cancer in New Jersey who also had a prior diagnosis of diabetes and/or hypertension (N = 228). Following breast cancer diagnosis, we examined types of practice setting for first primary care visit and primary breast surgery, through medical chart abstraction, and identified whether care was used within or outside the same health system. We used multivariable logistic regression to explore sociodemographic and clinical factors associated with care fragmentation. RESULTS: Diverse primary care settings were used: medical groups (32.0%), health systems (29.4%), solo practices (23.7%), Federally Qualified Health Centers (8.3%), and independent hospitals (6.1%). Surgical care predominately occurred in health systems (79.8%), with most hospitals being Commission on Cancer–accredited. Care fragmentation was experienced by 78.5% of Black women, and individual-level factors (age, health insurance, cancer stage, and comorbidity count) were not associated with care fragmentation ( P > .05). CONCLUSION: The majority of Black breast cancer survivors with comorbidities received primary care and surgical care in different health systems, illustrating care fragmentation. Strategies for care coordination and health care delivery across health systems and practice settings are needed for health equity.